Chronic osteomyelitis treatment with PerOssal®: a literature review - I Kadek Riyandi Pranadiva Mardana; Anak Agung Ngurah Ronny Kesuma; I Komang Agus Krisna Saputra; I Komang Mahendra Laksana (DiscoverSys Inc., 2022)
Chronic osteomyelitis is an inflammatory process in the bone followed by bone destruction caused by microorganism infection. The annual incidence of osteomyelitis is approximately 21.8 cases per 100,000 person-years in the general population. Implanting antibiotic-loaded carriers directly at the site of infection becomes a promising treatment approach. PerOssal® is an osteoconductive synthetic bone substitute for restoring and filling bone defects. PerOssal® pellets contain 51.1% nanocrystalline hydroxyapatite and 48.5% calcium sulfate. It has a role as bone material to fill bone defects caused by dead bone in chronic osteomyelitis. The porosity of PerOssal® allows a high initial antibiotic release, then decreases to ensure a local concentration of the antibiotic. PerOssal® did not show any in vitro cytotoxicity and fatal adverse event as bone material. PerOssal® is a promising antibiotic-loaded carrier for the management of chronic osteomyelitis. It demonstrates good biocompatibility with initial high antibiotic release without in vitro cytotoxicity and fatal adverse event.